The Impact of Posture on Wrist Tendinosis Among Blue-Collar Workers: The San Francisco Study. (February 2014) - Harris-Adamson, Carisa; You, Doohee; Eisen, Ellen A.; Goldberg, Robert; Rempel, David
Objective: The objective was to evaluate the effect of wrist posture on incidence of wrist tendinosis in a prospective cohort of blue-collar workers. Background: Previous studies have identified awkward wrist posture as a risk factor for wrist tendinosis, though the magnitude of the relationship is unclear. Method: Workers ( N = 413) at four industries were followed for up to 28 months with questionnaires and physical examinations every 4 months. Individualized exposure assessments of wrist posture were based on video analysis to determine the wrist extension/flexion angle for up to four tasks. Posture measures were calculated while in "heavy pinch" (> 1 kg force), "heavy power grip" (> 4 kg force), and across "all grips." A proportional hazards model estimated the relationship between time-weighted average posture measures and incidence of dominant-side wrist tendinosis. Results: In a model based on tertiles of exposure, adjusted for age, gender, hand force, and repetition of exertions, risk of tendinosis more than doubled in the highest category (HR = 2.69, 95% CI = 1.01–7.21) across all grips. The relative risk was highest during heavy pinch (HR = 5.03, 95% CI = 0.74–34.05), though not statistically significant. Increased median wrist extension while in heavy power grip was protective (HR = 0.24, 95% CI = 0.06–0.94). Conclusion: In this study of production workers, median wrist flexion of more than 7°, across all grips, was associated with an increased risk of tendinosis. The protective findings on median wrist extension during power grip deserve further investigation. Work tasks and tools should be designed to prevent sustained wrist flexion, especially during tasks involving forceful pinch.